Os impactos da MP 579, convertida na lei 12.783, nos investimentos em geração de energia do Brasil - Marques, Paloma Andrade (2014)
The year 2012 was a milestone for the Brazilian electricity sector. It was a year of many surprises, debates and paradigm shifts. The sector was previously an example of stability and conservatism became the target of questions and criticism from different agents, investors, traders, consumers and governments. Regulatory basis of the brazilian electricity sector is very recent. However it is notable that there has been progress in recent decade, in favor of a better service to the population and the development of a good environment for investment. Both goals were followed by a greater concern about meeting energy demand, growing in the country, and low tariffs aiming no inflationary impacts. Despite this path, the issue of MP 579 in September 2012 led to an environment of uncertainty for new investments due to doubts about many rules sanctioned consequence of insufficient debate with the private sector. The MP had the ambition to reduce the electricity tariff paid by the final consumer, and used as the main mechanism to nonrenewal of concessions of power generation, a possibility provided in each plant concession contracts. This thesis analyzes the power generating sector in Brazil. Its energy matrix, framework of the regulatory model adopted, its evolution in recent decades, and motivation for the enactment of MP is studied. The main goal is to study its impact on investments in the sector.